2020
DOI: 10.1002/ctpp.202000091
|View full text |Cite
|
Sign up to set email alerts
|

Propagation properties of dust‐electron‐acoustic waves in weakly magnetized dusty nonthermal plasmas

Abstract: The linear and nonlinear properties of dust-electron acoustic waves (DEAWs) propagating in magnetized, collisionless, dusty plasma system containing inertial cold electrons, Maxwellian hot electrons, nonthermal ions, and arbitrarily (positively or negatively) charged stationary dust are investigated. The reductive perturbation technique is employed to reduce the basic set of fluid equations to the modified Korteweg-de Vries equation or Ostrovsky's equation, which governs the dynamics of small amplitude DEAWs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…[ 37–45 ] Particularly in plasma physics, several works have been dedicated to the effect of the nonextensivity of particles on the various nonlinear phenomena inherent to the nonlinear dynamics of acoustic waves in plasmas. [ 10,46–53 ] It has been found that the presence of nonextensive populations in plasma media plays an important role and affects the conditions required for the formation and existence of a variety of nonlinear waves.…”
Section: Introductionmentioning
confidence: 99%
“…[ 37–45 ] Particularly in plasma physics, several works have been dedicated to the effect of the nonextensivity of particles on the various nonlinear phenomena inherent to the nonlinear dynamics of acoustic waves in plasmas. [ 10,46–53 ] It has been found that the presence of nonextensive populations in plasma media plays an important role and affects the conditions required for the formation and existence of a variety of nonlinear waves.…”
Section: Introductionmentioning
confidence: 99%